Influence of Channel Fading and Capture for Performance Evaluation in Vehicular Communications - Shah, A. F. M. Shahen; Karabulut, Muhammet Ali; Ilhan, Haci; Tureli, Ufuk (IEEE CANADA, 2023)
Autonomy and intelligent transportation systems (ITSs) have recently received increased interest for vehicular ad hoc networks (VANETs). In addition, the impending 5G and 6G technologies will result in substantial advancements for VANETs. The IEEE 802.11p summarizes specifications of physical (PHY) and medium access control (MAC) layers for VANETs. Although IEEE 802.11p MAC performance has been investigated, analytical methods need improvement. Bit error and channel capture influence the performance of vehicular communications in real-world transmission. These effects are investigated separately in previous works. In this article, an extensive study is provided that integrates these two major factors. In VANETs, the influence of channel fading and capture on IEEE 802.11p is investigated analytically using a Markov chain model. For Nakagami-m, Rayleigh, and Rician fading channels, performance-impacting factors are considered, and the relationships between parameters as well as performance metrics are derived. The probability of unsuccessful and successful transmission, outage probability, probability of frame capture, throughput, bit error rate (BER), and delay terms are attained. Moreover, simulation results are provided, which verify analytical studies.
Keywords: Markov processes; Vehicular ad hoc networks; Throughput; Receivers; Delays; Rician channels; Decoding; Capture; channel fading; IEEE 802.11p; Markov chain model; vehicular ad hoc network (VANETs); SATURATION THROUGHPUT ANALYSIS; COOPERATIVE MAC PROTOCOL; OPTIMIZATION; IEEE-802.11; Computer Science; Engineering